1998
DOI: 10.1016/s0014-5793(98)00963-6
|View full text |Cite
|
Sign up to set email alerts
|

The double‐stranded RNA‐binding domains of Xenopus laevis ADAR1 exhibit different RNA‐binding behaviors

Abstract: We have cloned cDNAs encoding two versions of Xenopus double-stranded RNA adenosine deaminase (ADAR1). Like ADAR1 proteins from other species Xenopus ADAR1 contains three double-stranded RNA-binding domains (dsRBDs) which are most likely required for substrate binding and recognition of this RNA-editing enzyme. Analysis of mammalian ADAR1 identified the third dsRBD in this enzyme as most important for RNA binding. Here we analyzed the three dsRBDs of Xenopus ADAR1 for their in vitro RNA-binding behavior using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…The results shown herein that the wild-type ADAR1-a, -b, and -c variants and the dsRBM motif mutants of the ADAR1-b variant differ in their ability to edit the natural cellular GluR-B RNA substrate, together with the finding that the Xenopus ADAR1 dsRBM motifs exhibit different RNA-binding behaviors (48), support the notion that functionally distinct dsRNA-binding domains of ADAR1 (32,36) reflect the occurrence of different structures among potential RNA substrates that are bound and edited by ADAR1 isoforms. Our results indicate that changes in the region between the dsRBD domain and the catalytic domain of ADAR1 affects the editing efficiency of GluR-B RNA in a site-specific fashion but without altering site-selectivity per se.…”
Section: Discussionmentioning
confidence: 55%
“…The results shown herein that the wild-type ADAR1-a, -b, and -c variants and the dsRBM motif mutants of the ADAR1-b variant differ in their ability to edit the natural cellular GluR-B RNA substrate, together with the finding that the Xenopus ADAR1 dsRBM motifs exhibit different RNA-binding behaviors (48), support the notion that functionally distinct dsRNA-binding domains of ADAR1 (32,36) reflect the occurrence of different structures among potential RNA substrates that are bound and edited by ADAR1 isoforms. Our results indicate that changes in the region between the dsRBD domain and the catalytic domain of ADAR1 affects the editing efficiency of GluR-B RNA in a site-specific fashion but without altering site-selectivity per se.…”
Section: Discussionmentioning
confidence: 55%
“…The second dsRBDs of either xlADAR1 or Xlrbpa, two proteins of different RNA-binding specificities, were chosen. These dsRBDs proved to be the strongest binders in the respective proteins as judged by Northwestern assays, and thus seemed the ideal candidates for initial target recognition (Brooks et al 1998). Interestingly, our results indicate that binding sites on the RNA clones obtained by SELEX show structural similarities, but share no common motif or sequence homology.…”
Section: Mimicking Coevolution Of Rnas With Dsrbds By Applying Selexmentioning
confidence: 78%
“…Moreover, Xlrbpa exhibits RNA chaperonin activity (Hitti et al 1998). The second dsRBD chosen for these experiments has the strongest RNA-binding activity in vitro and displays no apparent binding preference (Brooks et al 1998). On the other hand, the second dsRBD of Xenopus (xl) ADAR1, which also showed the strongest in vitro RNA-binding activity in this protein, was chosen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search results showed that the HYL1 protein contains two regions with marked similarities to dsRNA binding motifs (St. Johnston et al, 1992;Bass et al, 1994). The highest scoring segment pairs were those matching the dsRNA binding domains of the human interferon-induced RNA-dependent protein kinase P68, Escherichia coli ribonuclease III, and Xenopus dsRNA adenosine deaminase (Burd and Dreyfuss, 1994;Kharrat et al, 1995;Brooks et al, 1998). The two dsRNA binding motifs of the HYL1 protein are shown aligned with those of other proteins in Figure 7B.…”
mentioning
confidence: 96%